Heterocyclic Synthesis Using Nitrilimines-Part 1 Synthesis of stituted Dihydro- and Tetrahydro-1,2,4,5-Tetrazines - M. Dalloul, Hany; M. Abu-Dia, Yousef; E. El-Sawi, Amtithal (Asian Journal of Chemistry, 2012)
The reaction of C-phenylaminocarbonyl-N-arylnitrilimines (2a, b) with 1-stituted-1-methylhydrazines (3-7) afford the formation of the respective amidrazones (8a, b) when R = CH3, Ph, and to the acyclic adducts (9-11a, b) when R = —CHO, —COCH3 and —COOEt. The acyclic adducts underwent thermal oxidative cyclization at CH3 to give the unexpected 1,2,4,5-tetrazines (12-14a, b) rather than the expected tetrazinones (16a, b) when R = —COOEt. Dihydro-1,2,4,5-tetrazines (15a, b) were also separated when R = —CHO.